Intestinal microbiota regulates tryptophan metabolism following oral infection with Toxoplasma gondii. (3rd May 2020) - dos Santos, Liliane M.; Commodaro, Alessandra G.; Vasquez, Alicia R. R.; Kohlhoff, Markus; de Paula Guerra, Daniel A.; Coimbra, Roney S.; Martins‐Filho, Olindo A.; Teixeira‐Carvalho, Andrea; Rizzo, Luiz V.; Vieira, Leda Q.; Serra, Horacio M.
Abstract: Introduction: The intestinal microbiota plays an important role in modulating host immune responses. Oral Toxoplasma gondii infection can promote intestinal inflammation in certain mice strains. The IDO‐AhR axis may control tryptophan (Trp) metabolism constituting an important immune regulatory mechanism in inflammatory settings. Aims: In the present study, we investigated the role of the intestinal microbiota on Trp metabolism during oral infection with T gondii . Methods and results: Mice were treated with antibiotics for four weeks and then infected with T gondii by gavage. Histopathology and immune responses were evaluated 8 days after infection. We found that depletion of intestinal microbiota by antibiotics contributed to resistance against T gondii infection and led to reduced expression of AhR on dendritic and Treg cells. Mice depleted of Gram‐negative bacteria presented higher levels of systemic Trp, downregulation of AhR expression and increased resistance to infection whereas depletion of Gram‐positive bacteria did not affect susceptibility or expression of AhR on immune cells. Conclusion: Our findings indicate that the intestinal microbiota can control Trp availability and provide a link between the AhR pathway and host‐microbiota interaction in acute infection with T gondii .